Charge transfer and properties of localized plasmon resonance in Ag-TiO2 nanostructures - Д.А. Афанасьев; Н.Х. Ибраев; Э.Ж. Алихайдарова (Қарағанды университетінің хабаршысы. Физика сериясы)
In the paper the results of the synthesis of Ag – TiO2 nanostructures are presented. Nanostructures consist of a silver core and a TiO2 semiconductor shell. The size of nanostructures (NSs), determined by the method of dynamic light scattering, was 20 nm and 50 nm in different medias. The effect of the semiconductor shell of TiO2 on the properties of the localized plasmon resonance of silver nanoparticles is investigated. The quantitative index of localized plasmon resonance in NSs (electron density) was deteriorated, while the qualitative indicator of localized plasmon resonance (attenuation coefficient of plasma oscillations) can improve in the case of a thin TiO2 shell. After the synthesis of the TiO2 shell an additional luminescence band of the Ag – TiO2 NS is observed. The observed luminescence is associated with charge transfer from TiO2 on Ag. The dependence of the maximum recombination luminescence band on the value of the charge on silver nanoparticles is observed.